(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Aloe vera plant has been known as a miracle plant for centuries, owing to its health, beauty and medicinal properties. The term Aloe vera is derived from the Arabic word “Alloeh” which means “bitter shining substance,” while “vera” in Latin means “true”. The Egyptians called Aloe “the plant of immortality”. It is also called Quargandal, Ghritkumari, Gheekvar, katraazhai or kumari.